AN EFFECT OF CAPITAL ADECUACY RATIO (CAR) AND NON PERFORMING LOAN (NPL), ON STOCK RETURN WITH PROFITABILITY AS AN INTERVENING VARIABLE IN COMPANIES BANKS LISTED ON THE STOCK EXCHANGE INDONESIA - Moratia Suci Pratiwi; Rahima Br Purba (Jurnal Ekonomi, 2023)
This study aims to determine the effect of Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL) on Stock Returns with Return On Assets (ROA) as intervening variables in the banking sector in Indonesia. The sampling method used was purposive sampling and 46 banks were obtained. The data analysis technique used is path analysis which is the development of multiple and bivariate regression analysis. Partial research results show that the CAR variable has a positive and significant effect on profitability (return on assets). Partial research results show that the NPL variable has no significant effect on profitability (return on assets). Partial research results show that the CAR variable has a positive and significant effect on stock returns. Partial research results show that the NPL variable has no significant effect on stock returns. The partial results of the study show that the variable profitability (return on assets) has a positive and significant effect on stock returns. The results of the path analysis show that CAR and NPL indirectly have a positive and significant effect on stock returns through ROA.